(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2023)
Rhodium (III) interacts with thionine yellow in hydrochloric acid solutions. The formed ion associate could be extracted by the dychlorethan–carbon tetrachloride (2.5 + 2.5) plus aceton (5 mL) mixture, maximal extinction is observed at the value of wavelength 588 nm. Optimal acidity of aquas solutions is pH 1.0 by HCl. The optimal quantity of dye is 1.2–1.8 mL of 0,05% solutions. The coefficient of extraction is 98.6%. The range of determined concentration is 2.2–35.1 mcg of Rh(III) in 10 mL of aqueous phase. The value of seeming coefficient of thionine yellow tetrachlorrhodiate (III) ionic associates organic extracts molar extinction ε_588=1.05·104 L ·mol-1· cm-1 . The molar ratio beetwin thionine cation and tetrachlorrodiate (III) is 1:1.